Efektivitas Penerapan Aplikasi Edmodo Untuk Meningkatkan Literasi Digital Mahasiswa - Hasnawati, Hasnawati; Tarmizi, Pebrian; Anggraini, Dwi (UNIB Press, 2022)
This study aims to describe the effectiveness of implementing the Edmodo application and digital literacy for 5A semester students at the PGSD FKIP Study Program, Bengkulu University, for the Basic Concept of Dance. The research method used is action research conducted in 2 cycles. Data collection techniques are cognitive learning outcomes tests and digital literacy observations. Data analysis is using the classical absorption formula to analyze the effectiveness of learning and percentage techniques to analyze digital literacy. The results in this study were the classical absorption in cycle 1 was 73.75% and increased in cycle 2 by 85%. Digital literacy in cycle 1 is in the moderate category of 14.29%, good 63.64%, and very good 18.18%, increasing in cycle 2, namely 18.18% good category and 81.82% very good. Based on this, it can be concluded that the application of the Edmodo application is effective and can improve students' digital literacy.